PENERAPAN MEDIA PEMBELAJARAN BERBASIS GAME KAHOOT UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM KELAS VIII SMP NEGERI 20 MAKASSAR - Fajar, Muhammad; Nurlaelah; Mustamin; Abdul Karim, Bisyri; Fadhilah A Natsir, Andi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to describe the implementation of Kahoot game-based learning media and examine its role in improving students' learning outcomes in Islamic Religious Education for Grade VIII students at SMP Negeri 20 Makassar. The study was motivated by the low learning outcomes of students, whose classroom instruction had not yet utilized technology-based media and still relied on lecture methods with a whiteboard and printed textbooks, resulting in low student engagement and boredom during lessons. This research employed Classroom Action Research (CAR) conducted in two cycles, with each cycle consisting of two meetings. The subjects of this study were 30 Grade VIII students at SMP Negeri 20 Makassar. Data were collected through observation, interviews, tests, and documentation, and analyzed using percentage and mean-score calculation techniques for both student activity sheets and learning mastery. The findings indicated that the implementation of Kahoot contributed positively to the learning process and progressively improved students' learning outcomes, with the mean score rising from 66.2 (fair, 33.33% mastery) in the pre-cycle stage to 77.4 (good, 66.66% mastery) in Cycle I, and reaching 88.5 (excellent, 83.33% mastery) in Cycle II. Therefore, Kahoot-based game media can be considered an effective alternative for improving learning outcomes in Islamic Religious Education